2002
DOI: 10.1128/mcb.22.15.5443-5450.2002
|View full text |Cite
|
Sign up to set email alerts
|

p68 RNA Helicase Is an Essential Human Splicing Factor That Acts at the U1 snRNA-5′ Splice Site Duplex

Abstract: Modulation of the interaction between U1 snRNP and the 5 splice site (5ss) is a key event that governs 5ss recognition and spliceosome assembly. Using the methylene blue-mediated cross-linking method (Z. R. Liu, A. M. Wilkie, M. J. Clemens, and C. W. Smith, RNA 2:611-621, 1996), a 65-kDa protein (p65) was shown to interact with the U1-5ss duplex during spliceosome assembly (Z. R. Liu, B. Sargueil, and C. W. Smith, Mol. Cell. Biol. 18:6910-6920, 1998). In this report, p65 was identified as p68 RNA helicase and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
102
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(111 citation statements)
references
References 46 publications
8
102
0
1
Order By: Relevance
“…During the resting period, germ cells stop developing with only a small number of cells undergoing division and no mature sperm in the testes (Saffman and Lasko, 1999). Thus far, Cq-DDX5 has been functionally implicated as an essential factor required prior to the first catalytic step of cell differentiation (Liu, 2002). Therefore, these data support the hypothesis that Cq-DDX5 exerts a similar function in germ cell differentiation.…”
Section: Temporal Expression Of Cq-ddx5 In Ontogenesis and Spermatogesupporting
confidence: 77%
“…During the resting period, germ cells stop developing with only a small number of cells undergoing division and no mature sperm in the testes (Saffman and Lasko, 1999). Thus far, Cq-DDX5 has been functionally implicated as an essential factor required prior to the first catalytic step of cell differentiation (Liu, 2002). Therefore, these data support the hypothesis that Cq-DDX5 exerts a similar function in germ cell differentiation.…”
Section: Temporal Expression Of Cq-ddx5 In Ontogenesis and Spermatogesupporting
confidence: 77%
“…Our reporter assay confirms its function as a positive regulator of Gro-mediated repression as knocking down Rm62 resulted in attenuated Gro activity. Interestingly, Rm62 was also shown to be an essential splicing component through its action on the U1 snRNP (62,63). The possible significance of the spliceosome in Gro-mediated repression is discussed below.…”
Section: Gro Interactors Include Chromatin Remodelers Protein Kinasementioning
confidence: 99%
“…p68 is an established ATPase and RNA helicase (Hirling et al, 1989;Iggo and Lane, 1989) and has been shown to be involved in pre-mRNA splicing (Liu, 2002;Guil et al, 2003) and, in the case of the yeast homolog, Dbp2 (Iggo et al, 1991), to be important for both rRNA processing and nonsense-mediated mRNA decay (Bond et al, 2001). These functions in RNA processing/decay are consistent with p68 functioning as an RNA helicase.…”
Section: Introductionmentioning
confidence: 54%